SC Johnson Guardian™ spatial repellent shows 1-year efficacy against wild pyrethroid-resistant Anopheles arabiensis, with a similar blood-feeding inhibition efficacy to Mosquito Shield™ in a Tanzanian experimental hut trial - Swai, Johnson Kyeba; Ntabaliba, Watson Samuel; Mbuba, Emmanuel; Ngoyani, Hassan Ahamad; Makungwa, Noely Otto; Mseka, Antony Pius; Bradley, John; Chura, Madeleine Rose; Mascari, Thomas Michael; Moore, Sarah Jane (Frontiers in Malaria, 2025)
BackgroundSpatial repellents (SRs) that passively emanate airborne concentrations of an active ingredient within a space disrupt mosquito behaviors to reduce human-vector contact. A clinical trial of SC Johnson’s Mosquito Shield™ (Mosquito Shield) demonstrated a 33% protective efficacy against malaria in Kenya. Mosquito Shield lasts for 1 month, but a longer duration product is needed for malaria control programs. SC Johnson’s Guardian™ (Guardian) is designed to provide longer continuous protection from disease-transmitting mosquitoes.MethodsWe conducted experimental hut trials to i) evaluate the efficacy of Guardian over 12 months (between May 2022 and May 2023) and ii) assess the potential public health utility of Guardian by comparing it to Mosquito Shield over 1 month (midway through the Guardian evaluation in November 2022) against wild pyrethroid-resistant malaria vector mosquitoes. The primary endpoint was the number of blood-fed Anopheles arabiensis, while secondary endpoints were the proportion of dead An. arabiensis at 24 hours and the proportion of blood-fed mosquitoes. For Guardian, the number of mosquito landings was also evaluated by human landing catch, a method routinely used in community or implementation studies.ResultsOver 12 months of continuous use, Guardian reduced the number of An. arabiensis blood-feeding by 82.7% [95% confidence interval (78.5%–86.1%)] and landing by 65.1% (59.4%– 70.0%). Guardian also induced 20.1% mortality (18.4%–21.8%). Guardian was found to be superior to Mosquito Shield in reducing the number of blood-fed An. arabiensis with similar proportions of blood-fed and dead mosquitoes at 24 hours.ConclusionGuardian was effective in reducing blood-feeding and landing of wild pyrethroid-resistant malaria vectors for 12 months and shows superior protective efficacy compared to Mosquito Shield in reducing the overall number of blood-feeding mosquitoes. Experimental hut studies are suitable for comparative evaluations of new spatial repellent products because they precisely estimate entomological endpoints elicited by spatial repellents known to significantly impact vectorial capacity and disease transmission.